Population in economic growth - Pitchford, J. D. ([Amsterdam] : North-Holland Pub. Co.; New York : American Elsevier, 1974)
The objective of the book is to investigate questions involving the economics of population growth and in so doing help formulate growth theory in an appropriate way..
Includes bibliographical references.
uaa 25/01/19
Loans
Keywords: Population; Population--Mathematical models; Economic development